High sensitivity troponins in contemporary cardiology practice: are we turning a corner?. (2nd January 2018) - Mariathas, Mark; Olechowski, Bartosz; Mahmoudi, Michael; Curzen, Nick
ABSTRACT: Introduction: Troponin is considered to be the gold standard biomarker for ruling out MI. There has been a drive to improve the diagnostic speed, and as such the high sensitivity cardiac troponin (hs-cTn) assays have been introduced into clinical practice and are now part of international guidelines. Their novel value in clinical practice more generally is becoming apparent. Areas covered: In this review we will evaluate the evidence for the use of hs-cTn assays in clinical practice, the issues with the assay and how the hs-cTn can be utilized in the future as a biomarker of cardiovascular risk. Expert commentary: The use of the hs-cTn assays as a 'rule out' test for MI is compelling, as a 'rule in' there are significant issues relating the specificity of the assay for MI. The future of the assay may lie in population screening and risk modeling.